2012
DOI: 10.3390/ijms13055645
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Pinus nigra Arn. Populations in Southern Spain and Northern Morocco Revealed By Inter-Simple Sequence Repeat Profiles

Abstract: Eight Pinus nigra Arn. populations from Southern Spain and Northern Morocco were examined using inter-simple sequence repeat markers to characterize the genetic variability amongst populations. Pair-wise population genetic distance ranged from 0.031 to 0.283, with a mean of 0.150 between populations. The highest inter-population average distance was between PaCU from Cuenca and YeCA from Cazorla, while the lowest distance was between TaMO from Morocco and MA Sierra Mágina populations. Analysis of molecular var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
1
35
2
1
Order By: Relevance
“…Consequently, ISSR markers represent a powerful tool for investigating genetic variation within a species (Culley and Wolfe, 2001;Vicente et al, 2011;Rubio-Moraga et al, 2012). ISSR markers have been widely used for investigating population genetics in various plant species (Gajera et al, 2010;Wang et al, 2012;Zhang et al, 2013;Chen et al, 2013;Lin and Hu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, ISSR markers represent a powerful tool for investigating genetic variation within a species (Culley and Wolfe, 2001;Vicente et al, 2011;Rubio-Moraga et al, 2012). ISSR markers have been widely used for investigating population genetics in various plant species (Gajera et al, 2010;Wang et al, 2012;Zhang et al, 2013;Chen et al, 2013;Lin and Hu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the species is expected to be severely affected by the impacts of global change (temperature increase, irregularity of precipitation, drought, fire…), so its regeneration, growth and mortality are seriously jeopardized in many ecological contexts (Banquet et al, 2013;Tiscar and Linares, 2011), especially when carrying out forest restoration programs. Salzmann pine exhibits a high genetic diversity among populations most probably due to the geographic isolation and the fragmented (sub-) Mediterranean distribution of populations (Rubio-Moraga et al, 2012). This genetic diversity has to be considered in reforestation programs in the new context of climate change as genetic material based on local seed sources may become ineffective in the near future (Aitken et al, 2008;Breed et al, 2013;Williams and Dumroese, 2013).…”
mentioning
confidence: 99%
“…The Salzmann pine (Pinus nigra ssp. salzmannii) is an endemic subspecies of black pine native to the Western Mediterranean basin and covers 4 extensive areas of 350 000 ha in Spain (Rubio-Moraga et al, 2012). However, the species is expected to be severely affected by the impacts of global change (temperature increase, irregularity of precipitation, drought, fire…), so its regeneration, growth and mortality are seriously jeopardized in many ecological contexts (Banquet et al, 2013;Tiscar and Linares, 2011), especially when carrying out forest restoration programs.…”
mentioning
confidence: 99%
“…The highest H E values were observed in the Cong Troi population (0.250) and the lowest in the Hon Giao population (0.200; Table 5). Total genetic diversity for P. krempfii in this study (H E = 0.229) was higher than P. nigra (H E = 0.175) and Pinus squamata (H E = 0.029) (Zhang et al, 2005;Rubio-Moraga et al, 2012) and lower than some other Pinus species, which were similarly analyzed with ISSR markers, such as Pinus tabulaeformis (H E = 0.4152; Wang and Hao, 2010) Table 5). In all populations in the current study, five of the eight loci showed significant heterozygote deficiency.…”
Section: Genetic Divergencementioning
confidence: 45%